2019
DOI: 10.1364/boe.10.003463
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of individual bacteria using electro-photonic traps

Abstract: Antimicrobial resistance (AMR) describes the ability of bacteria to become immune to antimicrobial treatments. Current testing for AMR is based on culturing methods that are very slow because they assess the average response of billions of bacteria. In principle, if tests were available that could assess the response of individual bacteria, they could be much faster. Here, we propose an electro-photonic approach for the analysis and the monitoring of susceptibility at the single-bacterium level. Our method emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Importantly, we note that the advantage of using some of these indicators alternative to growth is also supported by other findings which do not necessarily use photonics, such as microfluidic techniques [25,119,133,134], AFM cantilever deflection [24,120,135] or electrochemical platforms [136][137][138]. For example, bacterial metabolism drives ionexchange across the membrane, so we see the measurement of electrical impedance at the single-cell level as a very promising method that could be added to the toolkit [90,136]. These observations suggest that a synergistic approach between different domains is desirable, as it might be able to provide even greater insight and meet important needs that still pose challenges.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Importantly, we note that the advantage of using some of these indicators alternative to growth is also supported by other findings which do not necessarily use photonics, such as microfluidic techniques [25,119,133,134], AFM cantilever deflection [24,120,135] or electrochemical platforms [136][137][138]. For example, bacterial metabolism drives ionexchange across the membrane, so we see the measurement of electrical impedance at the single-cell level as a very promising method that could be added to the toolkit [90,136]. These observations suggest that a synergistic approach between different domains is desirable, as it might be able to provide even greater insight and meet important needs that still pose challenges.…”
Section: Discussionsupporting
confidence: 59%
“…Antibiotic susceptibility is a multidimensional problem that can only be solved with a multiparameter approach. Several techniques have already recognized this need by measuring multiple responses in parallel, for example, morphology in conjunction with motility [25] or single-cell division [132,133], electrical impedance with motility [90] or bacterial division [138], as well as growth and motility [118].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrated optical devices have also been used for single bacteria analysis with label-free techniques [20]. In particular, resonant cavities are able to trap and identify single bacteria through the changes of the resonance response [21,22]. Emerging studies with a label-free optical-based approach have demonstrated real-time monitoring of cell attachment and the development of bacteria on the sensor surface [23].…”
Section: Techniques For the Bacteria Detection And Analysismentioning
confidence: 99%
“…However, this measurement approach cannot differentiate specific bacteria strains due to the overlapped refractive index variation of the bacteria. Conteduca et al used the silicon photonic crystal cavity with metal electrodes to trap single bacterium for antimicrobial resistance studies [69]. In addition to optical properties (transmission and resonance shift), the impedance of the surrounding medium is monitored, which is correlated to the metabolic rate in response to antibiotics.…”
Section: Light-particle Interactions For Biomedical Applicationsmentioning
confidence: 99%